American banks abroad : edge act companies and multinational banking - Baker, James Calvin; Bradford, Miles Gerald (New York : Praeger, 1974)
This book shows how American banks were expected to expand foreign operations in order to participate in and facilitate the multinational business growth
Includes bibliographical references and index.
mf 22/01/2019
Loans
Keywords: Banks and banking; Banks and banking, International; United States